Antioxidant response mechanism of freshwater microalgae species to reactive oxygen species production: a mini review. Issue 2 (7th February 2020) - Ugya, Adamu Yunusa; Imam, Tijjani Sabiu; Li, Anfeng; Ma, Jincai; Hua, Xiuyi
ABSTRACT: Molecular oxygen is essential to freshwater microalgae but its metabolic by-product known as reactive oxygen species (ROS) is toxic at higher levels leading to oxidative stress. Freshwater microalgae are able to prevent the effect of ROS using antioxidant response mechanisms. This mini-review is aimed at providing the progress and prospects of the antioxidant response mechanisms exhibited by freshwater microalgae to counteract excess ROS. The mini-review shows that the production of ROS and antioxidant response mechanism varies across species of freshwater microalgae and is dependent on factors such as freshwater microalgae cell size, cell shape, cell density, growth stage and abiotic factors such as light, nutrient, and temperature. This study also shows that freshwater microalgae are able to prevent oxidative damage resulting from a higher level of ROS production by the production of antioxidants. This antioxidant can be harness as phytonutrients that can be used as a health-promoting compound for the prevention of the risk of heart disease, cancer, and other diseases. More studies need to be done to ascertain the bioactive compounds that make up the antioxidant system of freshwater microalgae against excess ROS production and how these bioactive compounds can be utilised.